Unveiling social isolation in the daily life of the COVID 19 pandemic (Research, Society and Development, 2021)
COVID 19 is a pandemic with a serious impact on the health of the world population, with impairments in the psychosocial field of the population. The objective of the study is to unveil the experience of social isolation in the COVID 19 pandemic. For this, it carried out a mixed, quantitative and qualitative descriptive study, based on the hermeneutical phenomenological inspiration of language, in a virtual environment, with 231 volunteers, through the filling in an online form about the perception of everyday life in the COVID 19 pandemic. The data from the closed questions were analyzed by numerical frequency, while the open questions based on the hermeneutical phenomenological inspiration of language. The results show the general description of the participants and learning about COVID 19; the emotions and behaviors arising from the experience in the pandemic; and the common thematic nuclei about their experience in social isolation, with the production of meanings. Employees treat the COVID 19 pandemic and social isolation as a necessary and important, but not desirable process, with non-verbal language content associated with punitive processes, consequences of bad attitudes, of a common interpersonal practice already experienced, whatever the individuality and distance from intersubjectivity, considered a common process today.